ROCK SLOPE STABILITY ANALYSIS USING ROCK MASS CLASSIFICATION AND LIMIT EQUILIBRIUM METHODS ON THE PESONA NIRWANA RESORT, SOREANG SUBDISTRICT, BANDUNG DISTRICT, WEST JAVA - Hasan, Ferdi
Research location for rock slope stability analysis is located in the Pesona Nirwana tourist area, Panyirapan Village, Soreang Subdistrict, Bandung District. This research analyzed the stability of the slope with the Rock Mass Rating (RMR) classification method, kinematic analysis and Slope Mass Rating (SMR), and limit equilibrium method. Lithology of the study area consists of andesite and tuff. Physical and mechanical properties test results show that the average natural density of the rock ranges from 2.02 gr/cm3 to 2.72 gr/cm3 and the uniaxial compressive strength of whole rocks of 12.35 MPa to 207.02 MPa. Rock characteristics in the study area were obtained by horizontally spanning the scanline survey on the (LU), west slope (LS), and south slope (LS), and vertically on the north slope (SV). The results of calculations using the Rock Mass Rating (RMR) method show that LU, SV, LB, and LS slopes are included in class II (Good Rock). The results of the calculation using the Slope Mass Rating (SMR) method show that the LU, SV, LB, and LS slopes are included in class II (stable) until class III (partially stable) with a 20 – 40% probability of collapse. The highest probability of collapse based on kinematik analysis for the type of failure on the LU slope is a wedge failure, at the SV point is a plane failure (without boundaries), on the LB slope is a direct toppling, and on the LS slope is a plane failure (without boundaries). The safety factor value for the wedge failure of slope LU is 1,36, for the direct tipping avalanche of slope LB is 1,54, for the plane faillure (without boundaries) of slope LS is 1,37, and for the plane failure (without boundaries) at point SV is 1,51 so it can be concluded that all safety factor values are more than 1,3.